Evaluating Competency-Based Learning Outcomes of Public Health Graduates in Indonesia: A Case Study at Diponegoro University - Nurjazuli, Nurjazuli; Arso, Septo Pawelas; Muh, Fauzi (Universitas Negeri Semarang, 2025)
Background: Public health graduates are increasingly expected to possess not only theoretical knowledge but also practical competencies such as task execution, adaptability, and effective communication. In Indonesia, however, assessment practices predominantly focus on cognitive domains, often overlooking essential workforce competencies. Methods: This study employs a descriptive case study approach at the Faculty of Public Health, Diponegoro University, analyzing 18 group reports from the 2024 Field Learning Practice 2 (FLP_2) program. Assessment focuses on five competency dimensions defined by the Indonesian National Professional Certification Agency (BNSP): Task Skills (TS), Task Management Skills (TMS), Contingency Management Skills (CMS), Transfer Skills (TRS), and Job/Role Environment Skills (JRES). Results: Students demonstrated TS through systematic problem identification using the Multiple Criteria Utility Analysis (MCUA). TMS was evident in the planning and management of community interventions. CMS was reflected in effective responses to health crises, such as dengue outbreaks. TRS was noted for its ability to adapt to different socio-cultural environments. JRES was demonstrated through professional conduct in diverse institutional contexts. Authentic learning activities fostered readiness for complex public health roles. Conclusion: FLP_2 effectively evaluates comprehensive public health competencies. A shift towards performance-based, contextual assessment frameworks is essential for aligning education with workforce needs. Embedding such frameworks into curricula will enhance the quality and preparedness of graduates for addressing real-world challenges